Cryptoassets And the Deposit Guarantee Scheme: Regulatory Challenges and Implications for Financial Stability, With A Particular Focus on Stablecoins - Marcin GOSPODAROWICZ (Communications of International Proceedings, 2025)
This article addresses the role of stablecoins in the financial system, with particular emphasis on their potential as substitutes for bank deposits and the regulatory implications of this function. The theoretical part presents a classification of crypto-assets, discusses the relationship between stablecoins and electronic money, and outlines the theoretical basis for deposit substitution. The regulatory analysis focuses on the European Union's framework solutions (MiCA, DORA, BRRD), the positions of international institutions (BIS, IMF, FSB), and a comparison of regulatory approaches in the EU and the US. In the empirical part, based on data from 2015–2024, the relationships between stablecoin capitalization and the dynamics of bank deposits in the US and the EU were examined using lagged regression models and event analysis. The results indicate a significant substitution effect, particularly in the United States, and greater resilience of the deposit system in the EU, which may be linked to a more comprehensive regulatory framework. The article argues that while stablecoins can enhance innovation and payment efficiency, covering them with deposit guarantees poses serious risks to financial stability and monetary policy transmission. The conclusions point to the need for a balanced regulatory approach that ensures the transparency and security of stablecoins without undermining the foundations of the traditional banking system.
Keywords: stablecoins; cryptoassets; electronic money; deposit guarantees; deposit substitution; financial regulation